Synergistic effects of gene polymorphisms of the renin–angiotensin–aldosterone system on essential hypertension in Kazakhs in Xinjiang. (2nd January 2016) - Niu, Shudong; Zhang, Bin; Zhang, Keyong; Zhu, Pengcheng; Li, Jingping; Sun, Yujing; He, Ning; Zhang, Mingtao; Gao, Zhiying; Li, Xueyan; Simayi, Amuti; Ge, Jie; et al.
Abstract: Objective : To assess the synergistic effects of gene polymorphisms of the renin–angiotensin–aldosterone system (RAAS) on essential hypertension (EH) in Kazakhs in Xinjiang. Methods : A cross-sectional case-control association study was conducted in 52 1 hypertensive and 623 normotensive subjects of Kazakh ethnicity on eight common single nucleotide polymorphisms (SNPs) interspersed over five genes of the RAAS. SNPs were genotyped by polymerase chain reaction-restriction fragment length polymorphism. Interactions among the SNPs were analyzed by the multifactor dimensionality reduction method (MDR). Results : In single-locus analysis, subjects with AGT -6G, ACE D, and CYP11B2 -344C had increased susceptibility to EH (OR: 1.249; 1.425; 1.201). When subgrouped by sex, males with the t allele of REN Taq I had decreased risk for EH (OR: 0.529), and those with AGT -6G and CYP11B2 -344 C had increased risk for EH (OR: 1.498; 1.449). In females, carrying ACE D increased the risk for EH. (OR: 1.327). In six AGT haplotypes, H1 was protective, while H3 increased susceptibility to EH (OR: 0.683; 2.025). Interaction analysis by MDR showed that there was a strong synergistic effect between ACE I/D and CY11B2 (T-344C) and a moderate interaction between both ACE I/D and CY11B2 T-344C and AGT A-6G. Conclusions : There was a strong synergistic effect between ACE I/D and CY11B2 T-344C and a moderate effect between both ACE I/D and CY11B2 T-344C and AGT A-6G. AGT -6G, ACE D, and CY11B2 -344C increased susceptibility to EH. REN Taq I, AGT -6G, CY11B2 -344 C and ACE D were associated with male and female EH, respectively. H1 and H3 of AGT were protective and risk haplotypes, respectively.